2017
DOI: 10.1038/s41598-017-10126-2
|View full text |Cite
|
Sign up to set email alerts
|

The cellular and molecular determinants of emphysematous destruction in COPD

Abstract: The introduction of microCT has made it possible to show that the terminal bronchioles are narrowed and destroyed before the onset of emphysematous destruction in COPD. This report extends those observations to the cellular and molecular level in the centrilobular phenotype of emphysematous destruction in lungs donated by persons with very severe COPD (n = 4) treated by lung transplantation with unused donor lungs (n = 4) serving as controls. These lung specimens provided companion samples to those previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 42 publications
4
44
0
Order By: Relevance
“…This suggests that the alveolar destruction observed in COPD is driven by a Th1 response activated by infiltrating ILC1s. 85 …”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the alveolar destruction observed in COPD is driven by a Th1 response activated by infiltrating ILC1s. 85 …”
Section: Introductionmentioning
confidence: 99%
“…There may be differences in the pathogenesis between smoking-induced COPD and subjects with AAT deficiency. Whereas there is little doubt that smoking-induced COPD starts in the terminal bronchioles, 26 emphysema may be more predominant at an early stage in subjects with AAT deficiency. The PiZZ subjects in this study showed evidence of hyperinflation (high FRC/TLC ratios) and air trapping (high RV/TLC ratios), which may offer an explanation for our findings.…”
Section: Discussionmentioning
confidence: 99%
“…This airways inflammatory response spread to the lung parenchyma resulting in destruction of alveolar walls causing emphysema [11]. Inflammatory mediators resulting in persistent infiltrating immune inflammatory cells and their destructive enzymes have been implicated in the progressive destruction of the lung in COPD [12]. This destruction initiate remodeling that has been described in both the central airways, distal airways, and lung parenchyma.…”
Section: Pathobiology Of Copdmentioning
confidence: 99%